CITOMEGALOVIRUS (CMV) ENCEPHALITIS: A CASE REPORT - Meryana, Meryana (JURNAL WIDYA MEDIKA, 2022)
Encephalitis results from an inflammatory process in the brain which can be caused by infection, post infection or non-infection processes. The most common etiology is infection, especially by virus. Encephalitis is usually followed by diffuse and or focal neuropsychology dysfunctions of brain and meninges (meningoencephalitis). Symptoms of encephalitis are photophobia, headache or neck stiffness, focal neurological deficits, seizure, decrease of consciousness, behavior disorders, and aphasia. However, some patients may not show predominant neruological deficits or even asymptomatic. Inaccuracy to diagnose the etiology promptly can cause morbidity and mortality due to this disease. The author reports one case of citomegalovirus (CMV) encephalitis with mild symptoms. In this case, a 36-year old man with symptoms of mild fever and mild headache was consulted by an internist to neurologist, because internal examinations couldn’t find the etiology of the patient’s symptoms. The results of laboratory examinations of NS-1, Dengue IgM and IgG Dengue, Salmonella IgM and IgD, hepatitis screening tests, and chest X-ray examination showed normal results. Brain MRI with contrast then was performed with normal result. Cerebrospinal fluid (CSF) analysis showed pleiocytosis, predominantly mononuclear cells. Diagnosis of CMV encephalitis was established by examination of CMV PCR (Polymerase Chain Reaction) of CSF that was positive. The patient was then treated with antiviral agent Gansiklovir 5 mg/kg every 12 hours for 14 days. On the third day of therapy, the patients had been free of symptoms. The patient was discharged form the hospital in good condition.